Marketing Channels Efficiency Analysis of Scad (Decapterus sp.) Catches of Traditional Fishermen in Pengambengan Village Jembrana, Bali - Isukadana, Dita Dwi Ayu; Restu, I Wayan; Negara, I Ketut Wija (Advances in Tropical Biodiversity and Environmental Sciences, 2021)
Efficient marketing is characterized by low marketing margins and high farmer's share. This research was conducted to determine the condition and level of efficiency marketing channels Scad in Pengambengan Village during February-March 2020. The method used was descriptive qualitative method and quantitative descriptive by observation and interviews. Interviews were conducted with fishermen, collectors, wholesalers and retailers. The Marketing margin analysis and farmer's share were used to determine level of efficiency marketing channel. The results of the analysis show that there were two patterns of marketing channels for Scadthat were caught by traditional fishermen in Pengambengan Village. Marketing channel pattern I was a two-level channel pattern, while marketing channel pattern II was a three-level channel pattern. The marketing margin value in the two-level channel pattern was Rp5.700/kg with a farmer's share of 71%. The marketing margin value in the three-level channel pattern was Rp9.700/kg with a farmer's share of 59%. The marketing efficiency value obtained in two-level marketing channel pattern was 6%, while in three-level channel marketing pattern the marketing efficiency value was 8%. Based on the values obtained, the marketing efficiency of two-level channel pattern was as efficient as the three-level channel pattern. Thus, the marketing of Scad that were caught by traditional fishermen in Pengambengan Village was classified as efficient marketing.